Pacto Nacional pela Alfabetização na Idade Certa (PNAIC): formação continuada e práxis docente - Cruz, Juliane Barssalos da (2022)
This study is linked to the Master's Program in Management and Educational Practices at Universidade Nove de Julho (PROGEPE – UNINOVE). The object of study of this research is the PNAIC as a public policy aimed at training literacy teachers. The questions that guided the research were, namely: what changes occurred in the teaching practice of literacy teachers, after having participated in the continuing education of the PNAIC (2013-2016/2017-2018)? Were there advances in the teaching-learning process of students in the current PNAIC period (2013-2016/2017-2018)? Based on the questions, we outline the following general objective: to analyze the PNAIC and its contribution to the training of literacy teachers. Specific objectives are intended to: i) understand the PNAIC program and its formative assumptions; ii) observe the contributions of the PNAIC in relation to the pedagogical practices and in relation to the praxis of the teachers who participated in the program as scholarship holders; iii) discuss PNAIC's interference in the student learning process. The research universe was the ABC Paulista Region, located in the state of São Paulo and composed of the municipalities of Santo André, São Bernardo do Campo, São Caetano do Sul, Diadema, Mauá, Rio Grande da Serra and Ribeirão Pires. The research participants were twenty-nine teachers who taught, at the time of the PNAIC, in the first three years of Elementary School and who participated in the formation of the PNAIC between 2013 and 2017. The methodology used was qualitative and quantitative and, after document analysis, the data collection instruments used were: i) questionnaire with essay and multiple-choice questions and ii) semi-structured interview. The analysis of the results was based on the categorization based on Content Analysis proposed by Bardin (2011). The theoretical foundation of this research guides us scholars of public policies focused on basic education two who stand out: Stephen Ball (2004, 2009, 2011); Jefferson Mainardes (2006, 2018); Pierre Dardot and Cristian Laval (2017). On the influence of two multilateral organizations such as the World Bank and the Organization for Economic Cooperation and Development (OECD), stand out Olgaíses Maués (2003) and Eneida Oto Shiroma; Olinda Evangelista (2007). The theoretical reference for the continuous training of teachers is based on António Nóvoa (1999); Maurice Tardiff (2014); Umberto Pinto de Andrade (2006, 2018). On the aspects that base literacy in PNAIC, Magda Soares (2017) stands out; Roxane Rojo (2013, 2014); Maria do Rosario Longo Mortatti (2013). As results, it is verified that the PNAIC contributed with the training of two literacy teachers by promoting the mobilization of knowledge and transforming some aspects of their educational practices. In the ABC Paulista Region, the training has a participatory nature, in this way the teachers will share their knowledge and experiences, being these moments the most cited in the research. However, some weaknesses are also pointed out, due to the discontinuity of the program and its materials and the superficial treatment of some themes presented in the training and the materials made available by the program.